Best Answer

Use the quadratic equation: x = (-b plusminus root(b2 - 4ac)) / 2a

In this case, a = 1, b = 9, c = 12.

Another answer:

x2+9x+12 = 0

When factorised by means of the quadratic equation formula:

(x+7.372281323)(x+1.627718677) = 0

Therefore the roots are: -7.372281323 and -1.627718677

Check that your answer is correct by multiplying out the brackets which should bring you back to x2+9x+12 = 0

Q: What are the roots of the equation x2 plus 9x plus 12 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is a quadratic equation in X, with two real roots.

-4,3 are the roots of this equation, so for the values for which the sum of roots is 1 & product is -12

(x-2)(x+12) = 0 x = 2 or x -12

The equation seems to equal 72.

12

Related questions

It is a quadratic equation in X, with two real roots.

-4,3 are the roots of this equation, so for the values for which the sum of roots is 1 & product is -12

(x-2)(x+12) = 0 x = 2 or x -12

The equation is y + 2 = 12.

The equation seems to equal 72.

12

The equation -7 plus 12 equals out to be five. This is a math problem.

It is: y = -4x+12

There is no equation. An equation is true, whereas the statement ( 5 + 7 = -12 ) is false.

y = 10

-0.5

Without an "equals" somewhere along the way, you only have an expression, not an equation.Without an equation, there is no question, and nothing to answer.